Evaluation of the biotechnological potential of Rhizobium tropici strains for exopolysaccharide production - Luque Castellane, Tereza Cristina [UNESP]; Franco Lemos, Manoel Victor [UNESP]; Macedo Lemos, Eliana Gertrudes de [UNESP] (Elsevier B.V., 2014)
Rhizobium tropici, a member of the Rhizobiaceae family, has the ability to synthesize and secrete extracellular polysaccharides (EPS). Rhizobial EPS have attracted much attention from the scientific and industrial communities. Rhizobial isolates and R. tropici mutants that produced higher levels of EPS than the wildtype strain SEMIA4080 were used in the present study. The results suggested a heteropolymer structure for these EPS composed by glucose and galactose as prevailing monomer unit. All EPS samples exhibited a typical non-Newtonian and pseudoplastic fluid flow, and the aqueous solutions apparent viscosities increased in a concentration-dependent manner. These results serve as a foundation for further studies aimed at enhancing interest in the application of the MUTZC3, JAB1 and JAB6 strains with high EPS production and viscosity can be exploited for the large-scale commercial production of Rhizobial polysaccharides. (C) 2014 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: Extracellular polysaccharide; Biopolymer; Rhizobiwn tropici; Pseudoplastic